2017
DOI: 10.1152/ajpcell.00006.2017
|View full text |Cite|
|
Sign up to set email alerts
|

(Pro)renin receptor mediates albumin-induced cellular responses: role of site-1 protease-derived soluble (pro)renin receptor in renal epithelial cells

Abstract: Proteinuria is a characteristic of chronic kidney disease and also a causative factor that promotes the disease progression, in part, via activation of the intrarenal renin-angiotensin system (RAS). (Pro)renin receptor (PRR), a newly discovered component of the RAS, binds renin and (pro)renin to promote angiotensin I generation. The present study was performed to test the role of soluble PRR (sPRR) in albumin overload-induced responses in cultured human renal proximal tubular cell line human kidney 2 (HK-2) ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 41 publications
4
51
1
Order By: Relevance
“…Moreover, mutagenesis in cleavage site of the S1P, not furin decreases sPRR production in cultured renal cells overexpressing PRR. These results suggest that S1P plays a dominant role in the generation of sPRR and this S1P-derived sPRR mediates albumin-induced cellular responses [35]. However, our results show that furin inhibition has no effect on the size shift of sPRR as reported by Nagagawa et al [34].…”
Section: Role Of Site-1-protease (S1p) In the Generation Of Sprrsupporting
confidence: 46%
“…Moreover, mutagenesis in cleavage site of the S1P, not furin decreases sPRR production in cultured renal cells overexpressing PRR. These results suggest that S1P plays a dominant role in the generation of sPRR and this S1P-derived sPRR mediates albumin-induced cellular responses [35]. However, our results show that furin inhibition has no effect on the size shift of sPRR as reported by Nagagawa et al [34].…”
Section: Role Of Site-1-protease (S1p) In the Generation Of Sprrsupporting
confidence: 46%
“…Earlier studies showed that the PRR cleavage process depended on furin or ADAM19 (10,22). However, recent studies by Nakagawa et al (23) and our group (24), in which different approaches were used, consistently identified site-1 protease (S1P) as the predominant or only source of sPRR production. This finding allowed evaluation of the involvement of S1P-derived endogenous sPRR in the current experimental model.…”
Section: Resultsmentioning
confidence: 88%
“…Earlier studies showed that the cleavage process depended on furin or ADAM19 (17,18). However, recent studies by Nakagawa et al (19) and our laboratory (20) using different approaches consistently demonstrate that site-1 protease (S1P) functions as a predominant source of sPRR production. In the present study, we attempted to define the role of S1P-derived sPRR in regulation of fluid homeostasis and to study the underlying mechanism involving V 2 R regulation.…”
Section: Introductionmentioning
confidence: 78%
“…Recent reports from our group and others have identified S1P as a predominant protease responsible for the generation of sPRR (19,20). Therefore, we examined the role of S1P-derived sPRR in mediating AVP upregulation of V 2 R expression in primary rat IMCD cells.…”
Section: Figure 1 Prr-mediated Avp Upregulation Of V 2 R Expressionmentioning
confidence: 96%
See 1 more Smart Citation